Pre-existing parasympathetic dominance seems to cause persistent heart rate slowing after 6 months of fingolimod treatment in patients with multiple sclerosis - Hilz, Max-Josef; Canavese, Francesca; de Rojas Leal, Carmen; Lee, De Hyung; Linker, Ralf A.; Wang, Ruihao (Clinical Autonomic Research, 2024)
Purpose: Vagomimetic fingolimod effects cause heart rate (HR) slowing upon treatment initiation but wear off with sphingosine-1-phosphate receptor downregulation. Yet, prolonged HR slowing may persist after months of fingolimod treatment. We evaluated whether cardiovascular autonomic modulation differs before and 6 months after fingolimod initiation between patients with RRMS with and without initially prolonged HR slowing upon fingolimod initiation. Methods: In 34 patients with RRMS, we monitored RR intervals (RRI) and blood pressure (BP), at rest and upon standing up before fingolimod initiation. Six hours and 6 months after fingolimod initiation, we repeated recordings at rest. At the three time points, we calculated autonomic parameters, including RRI standard deviation (RRI-SD), RRI-total-powers, RMSSD, RRI high-frequency [HF] powers, RRI and BP low-frequency (LF) powers, and baroreflex sensitivity (BRS). Between and among patients with and without prolonged HR slowing upon fingolimod initiation, we compared all parameters assessed at the three time points (analysis of variance [ANOVA] with post hoc testing; significance: p < 0.05). Results: Six hours after fingolimod initiation, all patients had decreased HRs but increased RRIs, RRI-SDs, RMSSDs, RRI-HF-powers, RRI-total-powers, and BRS; 11 patients had prolonged HR slowing. Before fingolimod initiation, these 11 patients did not decrease parasympathetic RMSSDs and RRI-HF-powers upon standing up. After 6 months, all parameters had reapproached pretreatment values but the 11 patients with prolonged HR slowing had lower HRs while the other 23 patients had lower parasympathetic RMSSDs and RRI-HF-powers, and BRS than before fingolimod initiation. Conclusion: Our patients with prolonged HR slowing upon fingolimod initiation could not downregulate cardiovagal modulation upon standing up even before fingolimod initiation, and 6 months after fingolimod initiation still had more parasympathetic effect on HR while cardiovagal modulation and BRS were attenuated in the other 23 patients. Pre-existing parasympathetic predominance may cause prolonged HR slowing upon fingolimod initiation.
CRIS-Team Scopus Importer:2024-10-18
Keywords: Active standing; Fingolimod; Heart rate slowing; Parasympathetic predominance; Relapsing–remitting multiple sclerosis; Sphingosine-1-phosphate receptor